Sustainable construction industry strategies in South Africa: Specialization vs Diversification - Lorimer, Brett Alan (Department of Construction Economics and Management, 2020)
The construction and Civil Engineering industry is characterized by high risks, but equally high returns. The dynamics and complexities of this industry and its cycles, make it an extremely volatile and difficult industry to operate within. This is evident in the number of construction companies currently struggling to remain solvent, have gone into business rescue, and filed for bankruptcy. This industry has historically struggled to position itself effectively to deal with a down turning macro-economic environment - When it is good, it is very good, but when it is bad, it is very bad. Typically, there have been two differing strategies – Specialisation and Diversification. Specialisation, on the one hand, enables contractors to fine-tune their skill set and gear their businesses accordingly, to enhance their competitive edge. However, the result is concentration risk. Diversification however, enables contractors to become more risk-averse, and thereby less sensitive to the extremes of the cyclical nature that the construction industry is characterised by. The application of portfolio theory to a portfolio of construction projects was investigated, advancing the existing research done by Kangari and Riggs. Whilst most research has been limited to listed construction company performance, this analysis differentiates itself as it focusses on the intrinsic performance of actual construction projects (assets), which together form a portfolio. The theory is motivated by the concept that in order to value the stock, one must value the business. Construction companies should pay more careful attention to the selection of their projects. Critically, they should avoid becoming heavily invested in one type of construction, but rather to find a balance that will provide diversified risk benefits. Becoming more diversified can be achieved by investing in different types of construction projects - reducing specific risk. However, the most diversified position can only be achieved when investing outside the field of construction completely, and thereby reducing not only specific risks, but systematic risks too. This enhances sustainability in a way that the construction industry has not yet experienced.